Are we ready to use anti-amyloid therapy in Alzheimer's disease? - Brucki, Sonia Maria Dozzi; César-Freitas, Karolina Gouveia; Spera, Raphael Ribeiro; Borges, Conrado Regis; Smid, Jerusa (Arquivos de Neuro-Psiquiatria, 2022)
Alzheimer’s disease (AD) is the most common neurodegenerative disease. Biomarkers have demonstrated that AD pathology exists over the disease continuum from a stage preceding symptoms over 15-25 years to the progressively more impaired symptomatic states, mild cognitive impairment (MCI), and dementia. Biomarkers include: amyloid (Aß), phosphorylated tau, and neurodegeneration. The plasma assays for Aß and tau show great promise for clinical and research use. This review has aimed not only to present the ATN diagnostic classification and the preclinical AD concepts in addressing some possibilities of cognitive assessment instruments, but also to briefly summarize the main anti-amyloid monoclonal antibodies studied in clinical trials. In addition, this paper presents a critical analysis by experts in cognitive neurology while addressing the question as to whether we are prepared for the anti-amyloid therapy era or not.
Keywords: Alzheimer Disease; Biomarkers; Dementia